Quality of hospital care and clinical outcomes: a comparison between the Lombardy Region and the Italian national data - Signorelli, Carlo; Pennisi, Flavia; Lunetti, Carlo; Blandi, Lorenzo; Pelissero, Gabriele (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Improving the quality and effectiveness of healthcare is a key priority in health policy. The emergence of the COVID19 pandemic has exerted considerable pressure on hospital networks, requiring unprecedented reorganization and restructuring actions. This study analyzed data from the Italian National Outcomes Program to compare some volumes and outcomes of public and private accredited hospitals in the Lombardy Region with national data. Study design. Observational study. Methods. A thorough examination of hospital outcomes between 2019 and 2021 was conducted, considering 45 volume indicators and 48 process and outcome indicators, comparing Lombardy with other Italian regions and public versus private accredited hospitals. Results. In 2020, Italy and Lombardy experienced a considerable reduction in overall hospital admissions, with Lombardy showing a deeper decline (21.3% compared with 16.0% in Italy). In 2021, both experienced a partial recovery, especially marked in the Lombardy region (+7.3%, compared with national data). Focusing specifically on the private sector in Lombardy, a recovery of +9.3% in hospitalization was observed. In the analysis of clinical outcomes, Lombardy outperformed the national average for 63% of the indicators in 2020 and 83.3% in 2021. Conclusions. The study shows the continuing decline in volumes compared to 2019 (pre-COVID), the excellent performance of hospitals in Lombardy and a relevant contribution for the volumes and the quality of outcomes of private accredited hospitals.